2014
DOI: 10.1186/s13012-014-0125-9
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the quantity and quality of searching for current best evidence to answer clinical questions: protocol and intervention design of the MacPLUS FS Factorial Randomized Controlled Trials

Abstract: Background & aimsFinding current best evidence for clinical decisions remains challenging. With 3,000 new studies published every day, no single evidence-based resource provides all answers or is sufficiently updated. McMaster Premium LiteratUre Service - Federated Search (MacPLUS FS) addresses this issue by looking in multiple high quality resources simultaneously and displaying results in a one-page pyramid with the most clinically useful at the top. Yet, additional logistical and educational barriers need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
2
8
0
2
Order By: Relevance
“…However, a recent study 14 of physicians equipped with iPod Touches (Apple, Inc), which are smaller but otherwise similar devices to the iPad tablet, showed a lower successful search rate (25%-50%) and shorter average search time (2-5 minutes) compared with our findings. In addition, the rate of all foreground searches, 15% of tablet uses in this study, compares favorably to a pilot study 23 that found medical doctors conducted 0.46 search per month on average (using mobile and desktop computer systems). On the basis of 118 foreground searches, and data representing approximately 35 months of clinical practice, our users averaged a much higher, 3.4 searches per month.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, a recent study 14 of physicians equipped with iPod Touches (Apple, Inc), which are smaller but otherwise similar devices to the iPad tablet, showed a lower successful search rate (25%-50%) and shorter average search time (2-5 minutes) compared with our findings. In addition, the rate of all foreground searches, 15% of tablet uses in this study, compares favorably to a pilot study 23 that found medical doctors conducted 0.46 search per month on average (using mobile and desktop computer systems). On the basis of 118 foreground searches, and data representing approximately 35 months of clinical practice, our users averaged a much higher, 3.4 searches per month.…”
Section: Discussionsupporting
confidence: 64%
“…This rate is consistent with the designation of “regular searchers” in a large, ongoing implementation trial. 23 Thus, users in our study searched more often, were more successful, and spent more time than previous findings.…”
Section: Discussionsupporting
confidence: 43%
“…Por su parte, 56 artículos, un 41% del total, fueron escritos por cuatro o más autores, lo que supone un alto grado de coautoría en este ámbito. Entre ellos destacan el de Rosi, Brighenti et al (2016) sobre el aprendizaje a través del juego (con nueve autores), el de Rosi, Dall'Asta et al (2016), sobre el uso de tecnologías en primaria (con diez autores), ambos para la intervención en educación nutricional; y el de Agoritsas et al (2014) sobre intervenciones múltiples mediante gamificación en estudiantes de medicina (con 13 coautores).…”
Section: Resultsunclassified
“…A nivel mundial, entre los países con mayor producción científica en este campo se destaca la posición predominante del continente europeo, especialmente los países más meridionales (Italia, España y Grecia, por orden de producción) que sugiere, tal vez, connotaciones relacionadas con el carácter o personalidad de estas naciones. De los resultados del análisis de los datos de coautoría de los trabajos publicados se resalta como significativo un alto grado de firmantes, lo que señala un cierto tejido o tendencia de colaboración entre los investigadores interesados en este campo, como muestra se puede indicar el trabajo de Agoritsas et al (2014) con 13 coautores.…”
Section: Discusión Y Conclusiónunclassified
“…They may not be able to structure their question into an answerable form; answers can be different according to the words that they use to search the database [8]. The lack of quick and easy identification of relevant online literature was also described by Agoritsas and colleagues (2014) [8]. Also, standard search engines (e.g.…”
Section: Introductionmentioning
confidence: 99%